The foot in chronic rheumatoid arthritis. - Vidigal, E (1975)
The feet of 200 consecutive admissions with classical or definite rheumatoid arthritis were studied. 104 were found to have pain or deformity. Clinical involvement of the joints was seen more often than radiological joint damage in the ankle, but the reverse was the case in the midtarsal joints. The metatarsophalangeal joints were involved most frequently both clinically and radiologically. Sixty per cent of the patients required modified shoes but only a third of these had received them. The need for more shoes is clear, and although this is a highly selected group of patients they were all under specialist care. The increased expenditure on special footwear would benefit the patient, firstly by improving ambulation, and secondly perhaps by reducing the number of operations necessary. Hallux valgus was very common and occurred with similar frequency to disease in the other metatarsophalangeal joints. Although not exclusive to rheumatoid arthritis, hallux valgus must have been caused for the most part by the rheumatoid arthritis and if so, then it is suggested that the provision of suitable shoes for patients may be less costly than subsequent surgical treatment.